Assessment of Chronic Obstructive Pulmonary Disease Patient’s Satisfaction with The Provided Pharmaceutical Care Services - Asmaa Shean; Gamal Abdel Rahman; Nagwa Sabri; Marwa Adel (Archives of Pharmaceutical Sciences Ain Shams University, 2022)
Background: Patient satisfaction is a significant indicator of high-quality pharmacy service delivery, and consequently, assessment of customer satisfaction is a crucial technique for identifying and filling gaps in pharmacy service delivery. Objective: Evaluation of chronic obstructive pulmonary disease (COPD) patients’ satisfaction with pharmaceutical care services in the chest department outpatient clinic, Ain Shams University Hospitals, Cairo, Egypt. Methods: A cross-sectional study utilizing a structurally designed questionnaire was conducted to measure COPD patient satisfaction with pharmaceutical care services. The questionnaire was filled out by thirty COPD patients, after 12 weeks of providing the pharmaceutical care services by the researcher (clinical pharmacist). It was a self-administered survey constituted of two main parts; the first one included the patients' demographic data, and the second part included several domains about various pharmaceutical care services. The questionnaire provided a 5-point Likert response scale system used in Arabic and English language. Results: Most of the patients’ responses were in the “Good” and the “Very good” categories, and the greater age median of the respondents was associated with a better rating of the services. Providing information about the side effects of the medications and the inhaler technique appeared to enhance patients’ satisfaction. Conclusion: The satisfaction of COPD patients towards the services provided by the clinical pharmacist in the chest outpatient clinic is only intermediate, the older aged patients seemed to be more satisfied with the services provided than their younger counterparts. Efforts should be performed to increase the patients' satisfaction with the clinical pharmacy services.